Systematic literature review: the effect of dairy milk on markers of recovery optimisation in response to endurance exercise - Russo, I.; Camões-Costa, V.; Gaskell, S. K.; Porter, J.; Burke, L. M.; Costa, R. J. S. (International Journal of Sports Science, 2019)
The food and fluid provided in the acute post-exercise period plays an essential role in endurance exercise recovery and adaptation. The current systematic literature review (SLR) aimed to identify and synthesize research that investigated the effect of dairy milk beverages in comparison to alternative post-exercise beverages on markers of `exercise recovery optimisation`, which may influence subsequent endurance exercise performance. Seventeen papers met the inclusion criteria. Quality assessment was undertaken using the Cochrane Collaboration`s tool for assessing risk of bias. Intervention beverages included fresh dairy milk (n= 3), chocolate flavoured dairy milk (n= 6), dairy milk-based sports beverages (n= 4), or a combination of the aforementioned beverages (n= 4). Results indicate dairy milk enhanced muscle protein synthesis (i.e., mixed fractional synthetic rate: 0.11%/h dairy milk vs. 0.08%/h control), and elicited similar rates of muscle glycogen resynthesis (5.9 mmol/kgWW/h) compared to a carbohydrate replacement beverage (7.6 mmol/kgWW/h). Seven studies investigated the effect of dairy milk beverages on hydration status, three of which found no differences in restoring net fluid balance after consumption of a dairy milk or dairy milk-based beverage compared to a carbohydrate-electrolyte beverage and (or) water, when consumed ad libitum. The remaining four studies observed a greater net fluid balance after consumption of a dairy milk or dairy milk-based beverage compared to an isovolumetric dose of a carbohydrate-electrolyte beverage and (or) water. To date, no study has investigated the effect of dairy milk consumption after endurance exercise on markers of immune competency or gastrointestinal status. Five studies observed enhanced time-trial or time-to-exhaustion performance (7.4% to 52.4%) with a dairy milk beverage compared to an isocaloric beverage, while another study found no differences. It is concluded that dairy milk may provide either comparable or superior recovery nutrition qualities with regards to muscle protein synthesis, glycogen replenishment, rehydration, and subsequent endurance exercise performance, when compared to non-nutritive, carbohydrate replacement, and (or) carbohydrate-electrolyte alternatives.